Penicillin susceptibility among Staphylococcus aureus skin and soft tissue infections at a children’s hospital - J. Chase McNeil; Lauren M. Sommer; Marritta Joseph; Kristina G. Hulten; Sheldon L. Kaplan (Microbiology Spectrum, 2024)
ABSTRACT Shortly after its introduction into clinical practice, Staphylococcus aureus isolates gained resistance to penicillin via the acquisition of β-lactamases. A number of centers have recently described an increase in the proportion of invasive methicillin-susceptible S. aureus (MSSA), which are also susceptible to penicillin (PSSA). Little data are available regarding the prevalence or impact of PSSA in skin and soft tissue infections (SSTI). Community-acquired MSSA SSTI isolates were obtained through a surveillance study at Texas Children’s Hospital from January 2017 to December 2021. A total of 200 random isolates underwent PCR for blaZ β-lactamase; blaZ-negative isolates then underwent penicillin susceptibility testing using macrobroth dilution. Isolates which were blaZ negative and had a penicillin MIC ≤0.125 µg/mL were regarded as PSSA with the remainder regarded as penicillin-resistant MSSA (PR-MSSA). All PSSA underwent multilocus sequence typing. Medical records were reviewed. The median age of subjects was 4.2 years (IQR: 1.6–10.5). PSSA accounted for 9% of isolates during the study period. PSSA and PR-MSSA cases were similar with respect to age, demographics, and rates of prior antibiotic exposure. PSSA isolates less often had vancomycin MIC ≥1.5 µg/mL. Furthermore, 39% of PSSA were variants of sequence type 1. In multivariable analyses, penicillin susceptibility was independently associated with both hospital admission and surgical intervention. PSSA account for a small but significant proportion of MSSA SSTI in children. Clinically distinguishing patients with PSSA and PR-MSSA SSTI is challenging. However, PSSA SSTI were independently associated with higher rates of hospital admission as well as the need for surgical intervention suggesting a significant clinical impact.IMPORTANCEThe vast majority of Staphylococcus aureus in the US are penicillin resistant with most clinical labs no longer reporting penicillin susceptibility for this organism. A number of centers, however, have reported increasing penicillin susceptibility among invasive S. aureus infections. Skin and soft tissue infections (SSTI) are far more common than invasive infections, yet the frequency and impact of penicillin-susceptible S. aureus (PSSA) in this population are uncertain. Through active surveillance at a children’s hospital, we found that 9% of methicillin-susceptible S. aureus SSTI isolates were PSSA. PSSA were independently associated with hospital admission for the management of SSTI as well as the need for debridement in the operating room. Given that most SSTI are managed in the outpatient setting, these findings suggest a clinical impact of this phenotype and the need for a reassessment of the value in susceptibility testing and potentially even treatment with penicillin.